Automatically generating realistic test input from web services - Bozkurt, M.; Harman, M. (2011 IEEE 6th International Symposium on Service Oriented System, 2011)
Generating realistic test data is a major problem for software testers. Realistic test data generation for certain input types is hard to automate and therefore laborious. We propose a novel automated solution to test data generation that exploits existing web services as sources of realistic test data. Our approach is capable of generating realistic test data and also generating data based on tester-specified constraints. In experimental analysis, our prototype tool achieved between 93% and 100% success rates in generating realistic data using service compositions while random test data generation achieved only between 2% and 34%.